Small Cell Carcinoma of Oral Cavity (Buccal Mucosa): A Rare Case Report - Kumar, Amit; Sood, Rachit; Prasath, Ramesh; Yadav, Akhilesh Chandra; Ravichandran, Nivedhan; Saikia, Rosy (Asian Journal of Medical Research, 2022)
Small cell carcinoma (SCC) is an exquisite head and neck cancer defined as a high-grade neuroendocrine tumor analogous to a Small Cell Lung Carcinoma (SCLC). In the head and neck region, it is commonly located in the larynx, followed by the sino-nasal tract, the salivary glands, the trachea, the oral cavity, and the oropharynx in descending order. To the best of our knowledge, limited case reports have been documented up to now with a questionable definitive treatment protocol. We report the fourth case of SCC of buccal mucosa, which was confirmed by histopathology and immunohistochemistry and a wide local excision performed.